Engineering geology of the Channel Tunnel - Harris, Colin S. (Thomas Telford, 1996)
The Channel Tunnel has been called the greatest engineering project of the century, overcoming a unique set of financial political and engineering challenges. This title concerns aspects of engineering geology of the Channel Tunnel.